Examining the effects of elevated CO2 on the growth kinetics of two microalgae, Skeletonema dohrnii (Bacillariophyceae) and Heterosigma akashiwo (Raphidophyceae) - Qin, Jiahui; Jia, Minjuan; Sun, Jun (Frontiers in Marine Science, 2024)
Carbon dioxide (CO2) serves as the primary substrate for the photosynthesis of phytoplankton, forming the foundation of marine food webs and mediating the biogeochemical cycling of C and N. We studied the effects of CO2 variation on the Michaelis-Menten equations and elemental composition of Skeletonema dohrnii and Heterosigma akashiwo. CO2 functional response curves were conducted from 100 to 2000 ppm. The growth of both phytoplankton was significantly affected by CO2, but in different trends. The growth rate of S. dohrnii increased as CO2 levels rose up to 400 ppm before reaching saturation. In contrast to S. dohrnii, the growth rate of H. akashiwo increased with CO2 increasing up to 1000 ppm, and then CO2 saturated. In addition, H. akashiwo showed a slower growth rate than S. dohrnii for all CO2 concentrations, aside from 1000 ppm, and the Michaelis-Menten equations revealed that the half-saturation constant of H. akashiwo was higher than S. dohrnii. An increase in CO2 concentration was seen to significantly affected the POC: Chl-a of both S. dohrnii and H. akashiwo, however, the effects on their elemental composition were minimal. Overall, our findings indicate that H. akashiwo had a more positive reaction to elevated CO2 than S. dohrnii, and with higher nutrient utilization efficiency, while S. dohrnii exhibited higher carbon fixation efficiency, which is in line with their respective carbon concentrating mechanisms. Consequently, elevated CO2, either alone or in combination with other limiting factors, may significantly alter the relative relationships between these two harmful algal blooms (HAB) species over the next century.